DIGITAL PARENTING: A MILLENIAL WAY ON SAFEGUARDING EARLY CHILDHOOD - Palintan, Tien Asmara; Asqia, Nurul; Nisya, Nurul (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
Today's technological advances present challenges not only to adults but have also targeted early childhood. So that parents play an important role in educating and protecting children in the digital era. This research aims to determine the description of digital parenting engaged by parents in early childhood. This research is a mixed methods research with a sample size of 50 respondents from various kindergartens in Parepare City, South Sulawesi. The  instrument used for quantitative data is a digital parenting questionnaire with a Likert scale aimed at measuring the digital parenting response of parents of early childhood, while qualitative data used interview guidelines to examine more deeply the efforts and steps taken by parents in educating and protecting AUD in the digital era. The data analysis technique used is a descriptive technique with percentages. The results showed that parents engaged digital parenting are based on the principles of digital parenting consisting of the principle of norms, the impact of digital technology and the impact of digital messages. Digital world parenting, then, becomes crucial to balance children's interaction with the real world and the environment, and to stimulate children's thinking as well. Therefore, it is imperative for parents to comprehend and implement digital parenting in order to exert greater control over their children's usage of digital gadgets through the establishment of parental guidelines. This study can serve as a valuable resource for parents in their efforts to enhance their role in educating and safeguarding children in the digital age.